Implication of Excessive Working Hours On The Risk of Worker Morbidity: Microeconomic Analysis Approach - Nopiah, Ririn (Cita konsultindo, 2025)
In the increasingly competitive modern era, excessive working hours have become commonplace in various industrial sectors. However, the increase in working hours often has a negative impact on workers' health. This study aims to examine the effect of excessive working hours on workers' morbidity in Bengkulu. Using data from the National Socio-Economic Survey (SUSENAS), this study uses the Instrumental Variable (IV) Probit analysis method to address the potential for endogeneity in the relationship between variables. The results show that excessive working hours have a positive and significant effect on the chance of increasing workers' morbidity by 9.7 percent. In addition, domicile factors, types of business fields and expenditures also contribute to the chance of morbidity status. This study emphasizes that excessive working hours have serious implications for workers' physical and mental health, so it is important to implement policies that support work-life balance and health promotion programs in the workplace.